2019
DOI: 10.33549/physiolres.933905
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression in Patients With Abdominal Aortic Aneurysm – More Than Immunological Mechanisms Involved

Abstract: Abdominal aortic aneurysm (AAA) is a serious condition of unclear pathogenesis and progression. Two samples were collected from 48 patients during AAA surgery. One sample was collected from the aneurysm, the other from the aneurysm proximal neck where the tissue did not exhibit any aneurysmal changes. Subsequently, gene expression profiles using microarrays (Illumina) were compared in RNA extracted from the samples. Overall, 2,185 genes were found to be upregulated and 2,100 downregulated; from which 158 genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Two T-helper cell subsets, Th1 and Th2 cells, mediate these different forms of immunity ( Li et al, 2018 ). Previous studies have suggested that Th1 is upregulated in AAA ( Prucha et al, 2019 ). The balance between Th1-type and Th2-type immune responses may influence the progression of many inflammatory diseases (including AAA) ( Schulte et al, 2008 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Two T-helper cell subsets, Th1 and Th2 cells, mediate these different forms of immunity ( Li et al, 2018 ). Previous studies have suggested that Th1 is upregulated in AAA ( Prucha et al, 2019 ). The balance between Th1-type and Th2-type immune responses may influence the progression of many inflammatory diseases (including AAA) ( Schulte et al, 2008 ).…”
Section: Discussionmentioning
confidence: 91%
“…The GO analysis of the above two modules showed that the T-helper 1-type immune response is a central pathway. In AAA, inflammatory processes play a crucial role, accompanied by cellular and humoral immunity ( Prucha et al, 2019 ). Two T-helper cell subsets, Th1 and Th2 cells, mediate these different forms of immunity ( Li et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment of pathways containing activated genes involved in inflammation and ECM degradation, such as the chemokine and cytokine signaling pathway, as well as the integrin signaling pathway, were detected. Both have previously been reported to be involved in the regulation of inflammation [ 16 ] as well as ECM cell interaction in the context of mechanotransduction in AAA [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, cytokine‐cytokine receptor interaction has been shown to induce a complex network of inflammatory signalling pathways, including NF‐κB, MAPK and the JAK/STAT (Luo, Zhao, Li, & Zhang, 2013). Overactivation of these pathways in aneurysmal tissue promotes phenotypic changes of T lymphocytes, macrophages and VSMC and up‐regulates the expression of genes involved in extracellular matrix degradation, oxidative stress and cell migration, further exacerbating inflammation and tissue injury (Ohno et al, 2018; Prucha et al, 2019).…”
Section: Introductionmentioning
confidence: 99%